2020
DOI: 10.1371/journal.pone.0230552
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder farmers’ knowledge and willingness to pay for insect-based feeds in Kenya

Abstract: Edible insects are increasingly being considered as sustainable alternatives to fish and soybean meals in animal feed because of their high nutritional quality and environmental benefits. However, successful introduction of a new product to the market depends on the target user's acceptance. Thus, evaluating the potential demand of insect-based feeds would provide relevant information for policy development. The present study assessed farmers' knowledge on edible insects as feed, their acceptance of integratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…This implies that awareness creation and dissemination is important in promoting use of IBF among chicken farmers in Kenya. Our findings are supported by [30,49] who reported that prior exposure to a particular insect positively contributed to farmers' willingness to use IBF. Similarly, the performance aspects of IBF were perceived to be more important by farmers who belonged to groups than those who were not members of any group.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This implies that awareness creation and dissemination is important in promoting use of IBF among chicken farmers in Kenya. Our findings are supported by [30,49] who reported that prior exposure to a particular insect positively contributed to farmers' willingness to use IBF. Similarly, the performance aspects of IBF were perceived to be more important by farmers who belonged to groups than those who were not members of any group.…”
Section: Discussionsupporting
confidence: 82%
“…Following [22], this study defines perception as the cognitive interpretation and understanding of the comparative characteristics of insect proteins in livestock feeds over conventional fishmeal and soybean protein. We build on the work of [30] who described the attitudes and knowledge of livestock farmers towards use of insects as a feed alternative in Kenya. This study examines the factors that can support behavioral change of livestock farmers with respect to improved and cost-effective insect-based feeds by synthesizing evidence collected from chicken farmers in Kiambu County, Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Insects are considered a valuable and innovative alternative to fish and soybean meals in animal nutrition due to their high content of high-quality protein, fat, minerals, vitamins and fibre [1]. In particular, the most promising species are represented by the black soldier fly (Hermetia illucens, HI) and the yellow mealworm (Tenebrio molitor, TM), thanks to their easy rearing systems and their ability to consume a wide range of organic side streams [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they assessed the effects of replacing fishmeal as feed component by BSF meal on pig and poultry production which resulted in good livestock performance and, because of lower costs of BSF meal as compared to fishmeal, in a better return on investment (Chia et al, 2020a;Chia et al, 2018a;Chia et al, 2019a;Chia et al, 2020b;Chia et al, 2018b;Chia et al, 2019b;Onsongo et al, 2018). They determined that, as long as the fly larvae can be reared on substrates that are a true waste stream, the production of fly larvae as feed will not interfere with food production and will provide a sustainable alternative for fishmeal.…”
Section: Experience In Kenyamentioning
confidence: 99%